Tuhan dalam Pergulatan Pemikiran Soekarno - Syarifuddin Syarifuddin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
The tendency for a godless human nature as beings created by god. Sukarno in his capacity as a president of the Republic of Indonesia, as well as a thinker and politician, participated gave an interesting discourse on the idea of god. God on Sukarno opinions is not only have twenty kinds of characteristic, but not infinite, the qur'an as a Muslims guide, when read, internalized, and kept in mind, in Sukarno opinions qur’an was enlighted humans to understand and appreciate the existence of god itself. In Sukarno opinions qur’an was revolutionized the human mind, brought a revolution in the view of qur’an can provide an answer the human mind. Sukarno also gave the idea of theological matters was very interesting to observe. Therefore, thinking of god in Soekarno belief different with other Muslims. In Sukarno opinions, god has infinite nature, god remains supreme, not spelled out. Sukarno life is not colored by islamic life, but his adult life has been a follower of Islam. To be a moeslim, Soekarno has traveled a long odyssey of the mind, tireless in his search for truth The tendency for a godless human nature as beings created by god. Sukarno in his capacity as a president of the Republic of Indonesia, as well as a thinker and politician, participated gave an interesting discourse on the idea of god. God on Sukarno opinions is not only have twenty kinds of characteristic, but not infinite, the qur'an as a Muslims guide, when read, internalized, and kept in mind, in Sukarno opinions qur’an was enlighted humans to understand and appreciate the existence of god itself. In Sukarno opinions qur’an was revolutionized the human mind, brought a revolution in the view of qur’an can provide an answer the human mind. Sukarno also gave the idea of theological matters was very interesting to observe. Therefore, thinking of god in Soekarno belief different with other Muslims. In Sukarno opinions, god has infinite nature, god remains supreme, not spelled out. Sukarno life is not colored by islamic life, but his adult life has been a follower of Islam. To be a moeslim, Soekarno has traveled a long odyssey of the mind, tireless in his search for truth